Perception of Tax Corruption and Service Quality on Taxpayer Compliance with Trust as an Intervening Variable - Sholichah, Amilatus; Umaimah, Umaimah (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This study aims to determine the effect of perception of tax corruption and quality of tax authorities services on taxpayer compliance with trust in the tax authorities as an intervening variable. In this study, researchers tested taxpayer compliance at KPP Pratama Gresik using independent variables, namely, the effect of perception of tax corruption and quality of tax services. The population in this study were all taxpayers in the city of Gresik, sampling using random sampling method and the number of samples was 100 respondents. This study used a questionnaire with taxpayer respondents. Testing was carried out using SEM-PLS. The results showed that the effect of perception of tax corruption did not affect taxpayer compliance, and the quality of tax authorities services did not affect taxpayer compliance. Meanwhile, trust in the tax authorities had a significant effect on taxpayer compliance. The results of the intervening test showed that the effect of perception of tax corruption did not affect but the quality of tax authorities services affected trust in the tax authorities. Trust in the tax authorities was unable to mediate the relationship between perception of tax corruption and taxpayer compliance, while trust in the tax authorities was able to mediate the relationship between quality of tax authorities services and taxpayer compliance.